DIVERSITY AND PATHOGENICITY OF FUSARIUM OXYSPORUM F. SP. CUBENSE (FOC) RACE 4, THE CAUSAL AGENT OF FUSARIUM WILT OF BANANA IN INDONESIA - , Arif Wibowo, Ir.,M.Agr.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Fusarium wilt of banana caused by Fusarium oxysporum f. sp. cubense (Foc) is one of the most damaging diseases in tropical banana cultivation. Even though fusarium wilt of banana can be found in many regions in Indonesia, disease spreading, genetic variability and biological aspect of the fungal pathogen have not been known in detail.The study was aimed to understand: (1) the spreading of Foc race 4 in Indonesia